Prevalence Of Disability In India-An Update - Agarwal, A K; Singh, J V; Agarwal, Monika (Indian Journal of Community Health, 2009)
Background: In recent years, there is growing realization among developing countries about the need to evolve suitable policies & programs for the welfare of the disabled. But the paucity of data on the size of population of the handicapped belonging to different categories, needed for understanding the magnitude of the welfare services for their rehabilitation, is a major impediment for evolving a realistic approach to their problems. Objectives : The objective is to present the prevalence of different disabilities with a focus on rural and urban differential in distribution, their age oj onset, etiology, and social status of disabled in the country. Methods: NSSO survey methodology. Mental retardation & mental illness was included first time in NSSO survey. Results: NSSO Survey indicates, India is having 18.49 million P WDforming about 1.8% ofthe total population. For every 100,000people there are 1755 PWD either mentally or physically disabled. About 10.63% PWD were having more than one type of disabilities. In rural & urban area about 8.4% & 6.1% of total estimated house holds respectively reported to have at least one PWD. The prevalence of locomotor disability is highest among all types of disabilities. About 55% PWD were illiterate and only 26% PWD were employed. Survey showed that 5% live with their spouse and 47%> were never married. Conclusions: India has a large population of disabled who are in need of education, employment, and rehabilitative services. Special focus is needed for rural areas.